2014
DOI: 10.1177/2158244014559022
|View full text |Cite
|
Sign up to set email alerts
|

Making Real the Dream of Education for All Through Open Schooling and Open Universities in Ghana

Abstract: Although the last three decades have witnessed astronomical increases in enrollment in basic education, the challenges of access, equity, and quality continue to confront countries, especially in sub-Saharan Africa. In Ghana, education sector policies and reforms have been unable to deal with low transition rates from primary to junior high schools, from junior high schools to senior high schools, and from senior high schools to tertiary level. Children and young students who are unable to continue fail to ree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It is worthy to acknowledge that many studies affirmed that climate is an interesting variable to be observed by educational practitioners and researchers in the areas of school administration and management, especially in the study of student academic achievement and teacher productivity (Adeogun & Olisaemeka, 2011;Cohen & Geier, 2010;Gottfredson, Gottfredson, Payne, & Gottfredson, 2005;Thapa, Cohen, Guffey, & Higgins-D 'alessandro, 2013).Variables of school system like management, community participation, working environment, governance and supportive school climate are attributed as determining factors that have highly essential contributions towards effectiveness (Duze & Ogbah, 2013), some of which were used to elucidate effectiveness by Hofman, Hofman, Gray, & Wendy Pan (2015); Ranson, Farrell, Peim, and Smith, (2005). This is because, climate is instrumental to improving motivation and commitment among teacher and in achieving positive school outcome (Tagoe, 2014;Thapa et al, 2013;Thapa et al, 2012;Werang, 2014;Yusof, 2012). Moreover, researchers like Adejumobi and Ojikutu (2013), Dagnew (2014) and Zahid (2014) have considered school climate as an essential factor in school improvement, teacher job performance and student academic performance.…”
Section: School Climate and Effectivenessmentioning
confidence: 99%
“…It is worthy to acknowledge that many studies affirmed that climate is an interesting variable to be observed by educational practitioners and researchers in the areas of school administration and management, especially in the study of student academic achievement and teacher productivity (Adeogun & Olisaemeka, 2011;Cohen & Geier, 2010;Gottfredson, Gottfredson, Payne, & Gottfredson, 2005;Thapa, Cohen, Guffey, & Higgins-D 'alessandro, 2013).Variables of school system like management, community participation, working environment, governance and supportive school climate are attributed as determining factors that have highly essential contributions towards effectiveness (Duze & Ogbah, 2013), some of which were used to elucidate effectiveness by Hofman, Hofman, Gray, & Wendy Pan (2015); Ranson, Farrell, Peim, and Smith, (2005). This is because, climate is instrumental to improving motivation and commitment among teacher and in achieving positive school outcome (Tagoe, 2014;Thapa et al, 2013;Thapa et al, 2012;Werang, 2014;Yusof, 2012). Moreover, researchers like Adejumobi and Ojikutu (2013), Dagnew (2014) and Zahid (2014) have considered school climate as an essential factor in school improvement, teacher job performance and student academic performance.…”
Section: School Climate and Effectivenessmentioning
confidence: 99%
“…Access to tertiary education is a challenge in Ghana and some qualified applicants are denied yearly due to spatial issues [57]. Technology-enabled learning is being used to alleviate the issue.…”
Section: M-learning Adoption Process At S2mentioning
confidence: 99%
“…Within education, the language was rather about creating a supporting architecture and offered recommendations and advice on policy creation and and planning and implementation methodologies (Ochoa et al, 2011;Wright and Reju, 2012;Khanna and Basak, 2013). Relatively few articles generated discussion on infrastructure related to costs (Selviandro, Suryani and Hasibuan, 2014), Internet (Mtebe and Raisamo, 2014a;Odinma et al, 2011) and sustainability (Tagoe, 2014) even though within the next section, these were identified as major barriers to open development adoption.…”
Section: 1mentioning
confidence: 99%
“…Some articles made claims about the relevance of their work to 'ordinary' citizens without speaking to them or considering the actual Internet access restrictions 'ordinary' citizens face in these countries (Matheus et al, 2014;Nugroho et al, 2015). In the education domain, openness is argued to reach students who fall through the cracks (Tagoe, 2014), but typically research examined how OER can support inclusiveness for students already in attendance (Hodgkinson-Williams and Paskevicius, 2012;Shyshkina, 2015). Furthermore, adoption literature that sampled teacher perspectives demonstrated evidence of skewed demographics towards men (Okonkwo, 2012), there is a great need to discuss this pervasive inequality within educational institutions.…”
Section: 4mentioning
confidence: 99%